Elites and Society / Second Edition - Bottomore Tom (Rouledge, 1993)
The great merit of this study lies in the way it examines the concepts of ''elite'' and ''ruling class'' and above all, centers its own analysis at the point where the political tendencies of this century intersect. The Elite: Concept and Ideology, From the Ruling Class to the Power Elite, Politics and the Circulation of Elites, Intellectuals and Managers and Bureaucrats, Tradition and Modernity: Elites in the Developing Countries, Democracy and the Plurality of Elites, Equality or Elites?, Into the Millennium, Bibliography, Name and Subject Index.